Komparatif Pemikiran Pendidikan Akhlak Perspektif KH. Ahmad Dahlan dan KH.Hasyim Asy’ari Tahun 2017 - Mujiburrahman, Mujiburrahman; Nilfaita, Jumaati (LP3M UNZAH GENGGONG, 2020)
ABSTRACK Morals are the main focus when someone acts and acts in social life. A person's good morals do not appear automatically but need to be nurtured and taught from an early age. Many factors can shape a person's character to be good or bad, including the factor of family as a person who is always beside him and has a direct influence on his / her environment. Education is essentially an effort to pass on values, which will help and determine mankind in living life, and at the same time to improve the fate and civilization of mankind. There are 3 problem formulations to be studied in this thesis, namely: (1) How is Moral Education in K.H. Ahmad Dahlan and K.H. Hasyim Asy'ari? (2) What are the differences and similarities of K.H.Ahmad Dahlan and K.H.Hasyim Asy'ari's Moral Education? and (3) How is the relevance of K.H.Ahmad Dahlan and K.H.Hasyim Asy'ari's Moral Education to Islamic education today? Therefore, moral education is very important during the modernization era like today. This is due to the development of technology and changing lifestyles. If moral education is not instilled in students from a young age, it is possible that students will plunge students into something that is not desired by the wider community. Therefore, the objectives of education are at least divided into two, namely education aimed at developing mental / spiritual aspects and education in a physical / physical nature. The purpose of education is trying to form a person with good quality physically and spiritually. Thus, conceptually education has a strategic role in shaping students to become qualified human beings, not only quality in terms of skills, cognitive, affective, but also spiritual aspects. Here the author will discuss moral education according to two very prominent figures. Apart from being the founders of the most influential Islamic organizations in society, they are also two figures who have more or less similarities and differences, namely K.H. Ahmad Dahlan and K.H. Hasyim Asy'ari. Keywords : Pendidikan Akhlak, KH. Ahmad Dahlan, KH. Hasyim Asy’ari